PENGINTEGRASIAN NILAI KEARIFAN LOKAL NGGUSUWARU PADA PROGRAM PENGUATAN PENDIDIKAN KARAKTER (PPK) DALAM MENCEGAH TINDAKAN KRIMINAL SISWA - Ahmad Yani; Fadilah Try Mursyid (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2026)
This study aims to determine the characteristics of the PPPK module after being integrated with the values ​​of Nggusuwaru local wisdom, test the practicality of the PPPK module, obtain a PPPK module based on Nggusuwaru local wisdom that is effective in preventing student criminal acts. This study is a research and development (R&D) model of Borg & Gall. The development procedures include: (1) preliminary study, (2) planning, (3) development of a hypothetical model, (4) review of the hypothetical model, (5) revision, (6) limited trial, (7) revision of trial results, (8) extensive trial, (9) revision of the final model, (10) dissemination. The developed PPPK module was tested on 140 students of SMKN 3 Kota Bima and SMAN 5 Kota Bima. Data collection in this study used documentation studies, interview guidelines, expert judgment questionnaires and practicality questionnaires. Data on the PPPK module were analyzed qualitatively and quantitatively (Mixmethod). The feasibility test of the PPPK module was analyzed by the average score. The PPPK module was validated by experts using a walkthrough technique. The results of the validation by curriculum experts obtained a total score of 98 with a feasibility percentage of 90.74% (very feasible), language experts obtained a total score of 146 with a feasibility percentage of 86.90% (very feasible), media experts obtained a total score of 99 with a feasibility percentage of 91.67% (very feasible), and cultural experts obtained a total score of 124 with a feasibility percentage of 93.94% (very feasible). The results of the practicality test for students obtained an average practicality result of the PPPK module based on Nggusuwaru local wisdom of 4.2 with a "practical" category. Meanwhile, the practicality test for teachers obtained an average of 5.0 with a "very practical" category. The results of the study concluded that the value of Nggusuwaru local wisdom can significantly prevent criminal acts by students.